Assessing JAKSTRAKAB: government platform for waste management in Simeulue Regency, Indonesia - Handayani, Sri Wahyu; Hajad, Vellayati; Ilhamsyah, Fadhil; Ikhsan, Ikhsan; Herizal, Herizal (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
This study aims to determine the implementation of waste management policies in Simeulue District. The method used is qualitative, while the informants are determined by purposive sampling. Data was collected through interviews and documentation. While data analysis is done by means of transcription, classification, and drawing conclusions, The results of the study show that the implementation of policies related to waste management, abbreviated as Jakstrakab, as stated in Simeulue Regent Regulation Number 21 of 2019, shows that: (1) Jakstrakab communication through outreach has not reached many groups; (2) resources are still limited, especially related to human resources, budget, and waste management facilities such as abandoned fleets, warehouses, and equipment; (3) regarding the disposition, there is still overlapping work; and (4) the large bureaucratic structure causes officers to carry out their duties and functions not in accordance with the established Jakstrakab. The study concludes that bureaucracy, commitment, efficient communication, and resource allocation are necessary for Simeulue's waste management policy to be implemented. It is necessary to overcome obstacles including poor communication, a lack of resources, and bureaucratic disarray. Simeulue may enhance waste management practices toward sustainability by strengthening communication, managing resources better, and enlisting the support of policy implementers.